Pengoptimalan Pelaksanaan Pembangunan Desa melalui Pendampingan Perumusan Dokumen Perencanaan - Hartono Mamu; Regina Valentine Aydalina (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2021)
The success of “Developing Villages” is very much determined by a careful planning that is able to answer problems and anticipate opportunities and challenges that arise carefully and in the process carried out in a participatory manner by involving all stakeholders including the community and village officials/apparatus.The method used in the implementation of the Thematic Village Community Service Program is mentoring. At the end of this activity, a village planning document was obtained in the form of a Village Program Work Plan (RKPD) with the village priority program being the provision of clean water. In addition, students carry out additional activities in the village, namely Takraw Competitions between hamlets as an effort to strengthen the sense of brotherhood among residents.